Hymenopterous parasites associated with Phyllonorycter blancardella [Lepidoptera: Gracillariidae] in Nova Scotia and Quebec - Bishop, S.D.; Smith, R.F.; Vincent, C.; Goulet, H.; Huber, J.; Gibson, G.; Sharkey, M.; Borden, J.H. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2001)
Mined leaves were collected in commercial and unsprayed (no insecticides) apple orchards of Quebec and Nova Scotia to determine the relative abundance and diversity of parasites of the spotted tentiform leafminer, Phyllonorycter blancardella [Lepidoptera: Gracillariidae]. In Quebec, 29 species of leafminer parasites were recovered, belonging to 7 families: Aphelinidae, Braconidae, Chalcidae, Eulophidae, Ichneumonidae, Pteromalidae and Scelionidae. The most prevalent species were Pholetesor ornigis (67%), Sympiesis marylandensis (11%), S. serviceicornis (7%), Pnigalio maculipes (1.5%), Tetrasticus spp. (1.2%), while all other species accounted for < 1.0%. Pholetesor pedias, a braconid released in 1983 at Frelighsburg, Quebec, was not found in the 1984 and 1985 surveys. In Nova Scotia, 19 parasite species were recovered, belonging to 5 families : Braconidae, Encyrtidae, Eulophidae, Ichneumonidae and Pteromalidae. The most prevalent species were: Pholetesor ornigis (52%), Pnigalio maculipes (14%), Sympiesis serviceicornis (12%), S. marylandensis (9.5%), Sympiesis spp. (5%), Horismenus fraternus (1.8%), Paraleurocerus sp. (1.3%), Stictopisthus flaviceps (1.1%), while all other species accounted for < 1%. Seven and five species of hyperparasites were recovered in Nova Scotia and Quebec, respectively. New records for North America for the spotted tentiform leafminer as a host are : Sticopisthus bilineatus, S. flaviceps, Euderis sp., Pnigalio epilobii, P. pallipes and Paraleurocerus bicoloripes.